ECONOMICS ANALYSIS OF OPTIMAL MILK PRODUCTION IN SMALL-SCALE DAIRY FARMING IN YOGYAKARTA, INDONESIA - Arif, Himawan; Rachmansyah, Yanuar (Universitas Negeri Semarang, 2010)
Dairy farm, which produces calf and milk jointly, is expected to raise household’s income in rural areas where potential resources are available. This study aims at examing the optimal production of milk and calf by estimating a relationship between both productions. The study was conducted in Sleman,Yogyakartawhere dairy farms exist. Theory used in this study is economies scope in joint production. The results of study indicate that the level of joint production is still low such that there is no degree in economies of scope. Consequently, household’s income generated from this farm has not been maximised. To increase the income, it can be conducted by two consecutive steps. First, is to increase the production milk and calf jointly until the degree of economies of scope reached. Second, is to produce milk and calf in the best combination after reaching economies of scope. Recently, the best way to maximise income is to produce calf as low as possible, and to increase the period of producing milk.